In vivo enrichment of magnesium ions modifies sea urchin spicule properties. Issue 2 (June 2015) - Kanold, Julia Maxi; Lemloh, Marie-Louise; Schwendt, Peggy; Burghard, Zaklina; Baier, Johannes; Herbst, Frédéric; Bill, Joachim; Marin, Frédéric; Brümmer, Franz
Abstract : Sea urchin embryos produce an endoskeleton composed of two symmetric spicules that consist of calcite, containing approximately 5% magnesium. The function of magnesium ions in mineral formation in vivo and the consequence of their incorporation into the mineral on mechanical properties are largely unknown. The authors investigated the in vivo effects of excess magnesium ion concentrations in the medium on skeletal development of Arbacia lixula . Morphological deformations of pluteus larval spicules were observed after cultivation in Mg 2+ -enriched sea water. Energy dispersive X-ray spectroscopy showed that magnesium ions were homogeneously distributed for complete larvae and spicule cross-sections. Magnesium ion content was quantified by inductively coupled plasma optical emission spectrometry, which revealed a considerable increased incorporation of magnesium ions into spicules of larvae from Mg 2+ -enriched sea water. However, no change in crystal polymorph formation was observed by X-ray diffraction. Mechanical properties of spicule cross-sections were analysed by nanoindentation and revealed significantly higher stiffness values for spicules from Mg 2+ -enriched sea water compared to the control, whereas no significant change in hardness values was obtained. This in vivo study shows that increased magnesium ion incorporation into sea urchin larval spicules modifies the mineral properties and supports this model to investigate the effect of minor ions on biomineralisation.